Reagent-free analytical flow methods for the soft drink industry: Efforts for environmentally friendly chemical analysis - Thitirat Mantim; Phoonthawee Saetear; Saowapak Teerasong; Sumonmarn Chan-Eam; Kamonthip Sereenonchai; Natchanon Amornthammarong; Nuanlaor Ratanawimarnwong; Prapin Wilairat; Wanchai Meesiri; Kanchana Uraisin; Duangjai Nacapricha (My University, 2012)
The evolution of an entirely green analytical system for industrial quality control of carbonated drinks is described. The developed flow system is capable of providing analytical data of the dissolved CO 2 , sucrose, and color of a sample consecutively in real-time. The system has been carefully designed on the basis of “reagent-free”, meaning that no added chemicals are required for the analysis. The system first vaporizes CO 2 from the soft drink in a gas–liquid separation chamber, with a channel for a flow of pure water as the CO 2 acceptor. The dissolved CO 2 alters the conductivity of the water stream, which is directly related to the concentration of CO 2 in the soft drink. The sucrose content is measured based on the “schlieren effect”, the sample plug flows out of the vaporization chamber into a colorimeter with a near-infrared/light-emitting diode (NIR/LED) as light source. The schlieren effect arises at the boundary of pure water and soft drink with refraction of light in proportion to the sugar concentration. The system also measures the absorbance of the sample using an RGB-LED. The related principles and preliminary experiments as proof of concept are described as well as the construction of the flow system for this completely reagent-free analyzer. A simple flow injection system using the schlieren effect was also developed for rapid quantitative analysis of sugar in noncarbonated soft drinks.
Keywords: Colorimeter; Absorbance; Flow injection analysis; Microfluidic and Capillary Electrophoresis Applications